Pendampingan Metode Takrir dan Sambung Ayat dalam Meningkatkan Daya Ingat Hafalan Santri di PPTQ Al Hadi Imaan Dukun Gresik - Sholihuddin; Sho’idatul; M.aziz Shofiuddin; Rokhatin Ilma Navi’ah; Sri Windarti (Keris: Journal of Community Engagement, 2022)
Memorizing the Qur'an is one of the flagship programs at the Tahfidzul Qur'an Islamic Boarding School Al-Hadi Imaan Dukun Gresik. In a superior program, it is necessary to develop tahfidz to improve the quality of the superior program. This mentoring activity focuses on developing tahfidz in order to be able to assist in advancing superior programs. This mentoring activity uses methods that are in accordance with the environment, namely the takrir and verse linking methods which aim to improve the memory of memorizing the Qur'an. This assistance uses the ABCD (Asset Based Community Development) approach, which is an approach that emphasizes asset-based community development through the following stages: preparing; Discovery; dreams; define; and destiny. Mentoring the takrir and verse linking methods at the tahfidzul Qur'an al-Hadi imaan Islamic boarding school has made changes to the tahfidz program there, increasing the ability to memorize the Qur'an of students through the takrir and verse linking methods making students more active in memorizing and reviewing their memorization. And finally this Mentoring program became a flagship program at the Tahfidzul Quran Al Hadi Islamic Boarding School Imaan Dukun Gresik.